Reading the Market Genres of Financial Capitalism in Gilded Age America - Knight, Peter (Johns Hopkins University Press, 2016)
Americans pay famously close attention to "the market," obsessively watching trends, patterns, and swings and looking for clues in every fluctuation. In Reading the Market, Peter Knight explores the Gilded Age origins and development of this peculiar interest. He tracks the historic shift in market operations from local to national while examining how present-day ideas about the nature of markets are tied to past genres of financial representation.Drawing on the late nineteenth-century explosion of art, literature, and media, which sought to dramatize the workings of the stock market for a wide audience, Knight shows how ordinary Americans became both emotionally and financially invested in the market. He analyzes popular investment manuals, brokers' newsletters, newspaper columns, magazine articles, illustrations, and cartoons. He also introduces readers to fiction featuring financial tricksters, which was characterized by themes of personal trust and insider information. The book reveals how the popular culture of the period shaped the very idea of the market as a self-regulating mechanism by making the impersonal abstractions of high finance personal and concrete.From the rise of ticker-tape technology to the development of conspiracy theories, Reading the Market argues that commentary on the Stock Exchange between 1870 and 1915 changed how Americans understood finance-and explains what our pervasive interest in Wall Street says about us now.